2014
DOI: 10.1016/j.ijdevneu.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin induced neuronal differentiation: A boon for brain tumours

Abstract: The cumulative treatments of bovine lactoferrin (bLf) and iron saturated lactoferrin (Fe-bLf) in the neuroblastoma cells showed neuronal differentiating actions evident with the expression of specific differentiating markers, β-tubulin III and neurofilaments. The protein treatments also showed lowered endogenous survivin that is responsible for cell proliferation and the miRNA 584 and miRNA214-3p, required for differentiation. Further, bLf adopted the PI3K signalling predominantly, while Fe-bLf involved both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 55 publications
(58 reference statements)
2
12
0
1
Order By: Relevance
“…Milk consumption increases circulating insulin-like growth factor-1 and there is a positive association between this factor and depression [4]. Moreover, milk proteins such as lactoferrin impact neuronal differentiation [5], while milk whey protein alters brain mitochondrial activity and oxidative stress markers [6]. As these pathways are implicated in depression, we aimed to examine the relationship between milk intake and the risk for de novo MDD.…”
Section: Tablementioning
confidence: 99%
“…Milk consumption increases circulating insulin-like growth factor-1 and there is a positive association between this factor and depression [4]. Moreover, milk proteins such as lactoferrin impact neuronal differentiation [5], while milk whey protein alters brain mitochondrial activity and oxidative stress markers [6]. As these pathways are implicated in depression, we aimed to examine the relationship between milk intake and the risk for de novo MDD.…”
Section: Tablementioning
confidence: 99%
“…In addition to serving a key role in immune homeostasis, LF also reduces oxidative stress and may control excessive inflammatory responses (13,15,16). Recently, Sriramoju et al (17) reported that LF exerts various beneficial effects on humans and animals, including inhibition of carcinogenesis and prevention of drug-induced toxicity. Irradiated mice on an LF diet exhibited a significantly higher survival rate compared with mice fed a standard diet (18).…”
Section: Introductionmentioning
confidence: 99%
“…2,810 In addition, LF has been shown to have anti-angiogenic and anti-tumor properties, and most recently, essential roles in the neuronal differentiation. 2,11 While the mechanism for LF’s multipotency awaits further investigation, there is evidence suggesting that its anti-bacterial effect is conveyed in more than one way. LF confers its bacteriostatic activity on certain iron-dependent bacteria, including Escherichia coli , by sequestering available iron.…”
Section: Introductionmentioning
confidence: 99%